Podnebne spremembe in slovenski turizem - Turnšek, Maja (Geografski obzornik, 2023)
The target research project Climate change and sustainable development of Slovenian tourism analysed, among other things, tourism climate indicators. Temperatures are and will be higher, the precipitation regime is changing. Winter tourism is the most affected, as previous similar studies have shown. This article highlights the need for well-designed measures to adapt local tourism to a longer summer season, an increase in the frequency and intensity of heat waves, more frequent droughts and extreme events, as well as the social changes in tourist behaviour and market changes that can be expected in the tourist destinations.
Keywords: climate change; klimatske spremembe; Slovenia; Slovenija; tourism; trajnostni turizem; turizem